TECHNIQUES FOR TEACHING AND LEARNING VOCABULARY - Ikmatova Shakhnoza (Journals Park Publishing, 2022)
This article is devoted to the teaching and learning techniques of the vocabulary and how to use at the lessons and designing some different activities in teaching vocabulary.
Keywords: relia; techniques; eliciting words